I KNOW THEREFORE I ACT: SUSTAINABLE DEVELOPMENT AWARENESS AS A PREDICTOR OF MINDFUL CONSUMPTION - Herabadi, Astrid Gisela; Kadarusman, Yohanes B (MANASA, 2024)
The impact of non-sustainable lifestyle has increasedly being noticed and more attention are nowadays drawn toward the notion of establishing a more responsible consumption behaviour, mindful consumption is a form of that behaviour. The involvement of individuals, especially the younger generation, is much needed to meet the sustainable development goals of a nation, since it is not the responsibility of the government alone. People should have the notion that their independent participations in the areas of economic, societal and environmental activities will benefit the whole nation. Therefore, the aim of this study is to verify that individual awareness of their contribution to sustainable development will predict mindful consumption. A survey was conducted on 153 young adult participants who are university students, aged between 18 to 25 living in Jabodetabek area. The results show that sustainable development awareness in general significantly predicted mindful consumption, as individuals’ awareness of their role in sustainable development increase, so does their mindful consumption. Further analysis find that the economic dimension of sustainable development awareness is the strongest predictors of mindful consumption, followed with the society dimension. However, the environment dimension of sustainable development awareness does not seem to contribute as a significant predictor of mindful consumption. This study gives rise to an implication that sustainable development awareness should be included in the education of the public in general, specifically for young people, in the hope that it will encourage more mindful consumption pattern of the people to support sustainable development of a country.